My side of the mountain - George, Jean Craighead, 1919- (New York : Puffin Books, 2001)
A young boy relates his adventures during the year he spends living alone in the Catskill Mountains including his struggle for survival, his dependence on nature, his animal friends, and his ultimate realization that he needs human companionship.
"A Puffin book."
Keywords: Survival -- Juvenile fiction; Selfreliance -- Juvenile fiction; Mountain life -- Juvenile fiction